The f-commerce handbook : 10 secrets for unlocking the sales potential of Facebook - Marsden, Paul (McGraw-Hill, 2012)
The f-Commerce Handbook delivers practical guidance, proven strategies, and best practices to profit from Facebook as a direct sales channel. It reveals ten smart but simple secrets for running profitable sales events on Facebook, all designed and proven to build business and monetize efforts.